Aspects of anesthesia and resuscitation in wounds of the heart and great vessels - Peri, Homero (Cirugía del Uruguay, 1973)
Providing analgesia, hypnosis, muscle relaxation is just one more element in the management of a more complex and serious situation as it is in the patient with heart injuries and large vessels, where the fundamental objective is to preserve life by maintaining the most adequate volume of circulating blood possible.